Analisis Pengaruh Financial Indicators dan Ownership Structure untuk Memprediksi Kondisi Financial Distress (Studi pada Sektor Industri Perdagangan, Jasa, dan Investasi yang Terdaftar di BEI Tahun 2014-2018) - Elyia Rosiana Savitri; Purwohandoko Purwohandoko (Jurnal Ilmu Manajemen, 2021)
Financial distress is the stage when a company experiences a decline in financial performance before bankruptcy occurs. This study aims to examine the effect of financial indicators and ownership structure on financial distress. The independent variables in financial indicators include profitability, activity, growth, liquidity, and leverage. The ownership structure includes managerial ownership and institutional ownership. This research period is for five years, from 2014 to 2018. This study's population are companies in the trade, services, and investment sectors. Samples were taken using the purposive sampling method and obtained 16 companies as samples. The results of data analysis using the logistic regression method. The results showed that the current ratio and debt to assets ratio significantly affected financial distress. Meanwhile, the variables return on assets, total assets turnover, sales growth, managerial ownership, and institutional ownership do not significantly affect financial distress. The solution that the trade, service can carry out, and investment industry sector that has negative EPS in a row is to pay off short-term obligations within a predetermined period and maximize the benefits of debt as a tax deduction so that financial distress for companies can be avoided.